Growth and developmental outcomes of the extremely preterm infant - Rugolo, Ligia Maria Suppo de Souza [UNESP] (FapUNIFESP (SciELO), 2005)
Objetive: To provide information for pediatricians and neonatologists to create realistic outcome expectations and thus help plan their actions. Sources of data: Searches were made of the Cochrane Library, MEDLINE, and Lilacs databases. Summary of the findings: The assessment of growth and development over the first 2-3 years must adjust chronological age with respect of the degree of prematurity. There is special concern regarding the prognoses of small for gestational age preterm infants, and for those with bronchopulmonary dysplasia. Attention must be directed towards improving the nutrition of extremely low birth weight infants during their first years of life; these infants have high prevalence levels of failure to catch-up on growth, diseases and rehospitalizations during their first 2 years. They are frequently underweight and shorter than expected during early childhood, but delayed catch-up growth may occur between 8 and 14 years. Extremely low birth weight infants are at increased risk of neurological abnormalities and developmental delays during their first years of life. Educational, psychological, and behavioral problems are frequent during school years. Teenage and adult outcomes show that although some performance differences persist, social integration is not impaired. Conclusions: The growth and neurodevelopment of all ELBW infants must be carefully monitored after discharge, to ensure that children and their families receive adequate support and intervention to optimize prognoses. Copyright © 2005 by Sociedade Brasileira de Pediatria.
Keywords: Catch-up growth; Developmental outcome; Extremely low birth weight; Growth; Prematurity; adolescence; behavior disorder; catch up growth; Cochrane Library; cognition; developmental disorder; extremely low birth weight; growth disorder; growth retardation; hospitalization; human; low birth weight; lung dysplasia; MEDLINE; nerve cell differentiation; neurologic disease; perinatal development; postnatal development; prematurity; prevalence; prognosis; review; risk factor; short stature; small for date infant; sociology; underweight; child development; growth, development and aging; newborn; physiology; very low birth weight; Child Development; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Prognosis